2017
DOI: 10.1111/ped.13273
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor polymorphisms in immune thrombocytopenic purpura

Abstract: There appears to be an interaction between the Cdx-2 variant of VDR and childhood immune thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…3 The vitamin D receptor (VDR) gene can regulate immune responses in the body, inhibit abnormal cell activation, and maintain the stability of cell function. 4 A number of clinical studies have confirmed that vitamin D can effectively prevent and treat bronchial asthma by regulating the immune system, and both AR and bronchial asthma have similar etiology and pathogenesis and belong to the same category of diseases. 5,6 Changes in vitamin D levels in the body can regulate the immune system, and thus affect the occurrence of AR.…”
Section: Introductionmentioning
confidence: 99%
“…3 The vitamin D receptor (VDR) gene can regulate immune responses in the body, inhibit abnormal cell activation, and maintain the stability of cell function. 4 A number of clinical studies have confirmed that vitamin D can effectively prevent and treat bronchial asthma by regulating the immune system, and both AR and bronchial asthma have similar etiology and pathogenesis and belong to the same category of diseases. 5,6 Changes in vitamin D levels in the body can regulate the immune system, and thus affect the occurrence of AR.…”
Section: Introductionmentioning
confidence: 99%
“…The mean 25(OH)D value at ITP diagnosis in our study (65 ± 24 nmol/L) can be considered as hypovitaminosis D [47,48,55]. Liu et al reported a mean 25(OH)D value of 43 ± 13 nmol/L in adult patients with ITP, while Yesil et al reported a mean 25(OH)D value of 47 ± 21 nmol/L in children with ITP [56,57]. The higher values in our study might be explained with the difference in the geographic origin of the patients that were included in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Аллель А Cdx-2 полиморфизма ассоцииро-вался с уменьшением риска иммунной тромбоци-топенической пурпуры. Статистически значимой разницы между группой больных и контрольной группой для полиморфизмов Fok1, Bsm1, Apa1 и Taq1 (р>0,5) не обнаружено [30].…”
Section: обзоры литературыunclassified
“…Аллель А Cdx-2 полиморфизма ассоцииро-вался с уменьшением риска иммунной тромбоци-топенической пурпуры. Статистически значимой разницы между группой больных и контрольной группой для полиморфизмов Fok1, Bsm1, Apa1 и Taq1 (р>0,5) не обнаружено [30].Активно изучается роль различных вариантов ге-нотипов полиморфизма гена VDR в развитии и тече-нии бронхиальной астмы как у детей, так и у взрос-лых. Исследование M. Iordanidou и соавт.…”
unclassified